Penerapan Metode Analytical Hierarchy Process (AHP) pada Desain Pemanfaatan Kulong Kebintik - Sabri, Fadillah; Novriyansyah, Muhammad (MEDIA KOMUNIKASI TEKNIK SIPIL, 2023)
The purpose of this research is to design the utilization of the potential of Kulong Kebintik, in the form of the potential of Kulong water and the land around Kulong. The method used is a quantitative descriptive survey method. Most of the data used is in the form of secondary data, the primary data is only in the form of kulong water quality data. Quantitative Kulong Kebintik water is based on analysis using the Nreca model. has a monthly average debit of 114.7 liters/second. In terms of water quality, Kulong Kebintik is brackish because it is located close to the coast which is still affected by tides. Kulong water utilization analysis uses the Analytical Hierarchy Process (AHP) method. The basis for determining alternative designs for the use of kulong consists of four criteria in the form of; water availability, water quality, community demand, and cost. An alternative utilization of kulong is for raw water sources, tourism, and fisheries. Based on an analysis of all the criteria, the best Kulong utilization design is for fisheries (39%), then for tourism or recreation (32%), and finally for raw water sources (29%)